Desmoid fibromatosis of the chest wall. Issue 4 (28th February 2018) - Ong, QiHao; Wong, Janice; Sinha, Sanjay; Kejriwal, Nand
Abstract : We report a rare case of desmoid fibromatosis of the chest wall. Abstract : We report a case of desmoid fibromatosis of the chest wall. A 70‐year‐old woman was referred to our hospital with right shoulder blade pain and paresthesia over the right upper breast. Chest X‐ray and computed tomography demonstrated a 5 cm right apical mass in the chest. Biopsy of the mass demonstrated features of desmoid fibromatosis. The patient subsequently underwent surgical resection of the mass and received adjuvant radiation therapy for microscopic positive margins. In conclusion, although desmoid tumour of the chest is rare, it is worth considering in the differential diagnoses of chest wall tumours.